Clinical formulas, mother’s opinion and ultrasound in predicting birth weight - Torloni, Maria Regina; Sass, Nelson; Sato, Jussara Leiko; Renzi, Ana Carolina Pinheiro; Fukuyama, Maísa; Lucca, Paula Rubia de (São Paulo Medical Journal, 2008)
CONTEXT AND OBJECTIVE: Accurate fetal weight estimation is important for labor and delivery management. So far, there has not been any conclusive evidence to indicate that any technique for fetal weight estimation is superior to any other. Clinical formulas for fetal weight estimation are easy to use but have not been extensively studied in the literature. This study aimed to evaluate the accuracy of clinical formulas for fetal weight estimation compared to maternal and ultrasound estimates. DESIGN AND SETTING: Prospective study involving 100 full-term, cephalic, singleton pregnancies delivered within three days of fetal weight estimation. The setting was a tertiary public teaching hospital in São Paulo, Brazil. METHODS: Upon admission, the mother’s opinion about fetal weight was recorded. Symphyseal-fundal height and abdominal girth were measured and two formulas were used to calculate fetal weight. An ultrasound scan was then performed by a specialist to estimate fetal weight. The four estimates were compared with the birth weight. The accuracy of the estimates was assessed by calculating the percentage that was within 10% of actual birth weight for each method. The chi-squared test was used for comparisons and p < 0.05 was considered signifi cant. RESULTS: The birth weight was correctly estimated (± 10%) in 59%, 57%, 61%, and 65% of the cases using the mother’s estimate, two clinical formulas, and ultrasound estimate, respectively. The accuracy of the four methods did not differ signifi cantly. CONCLUSION: Clinical formulas for fetal weight prediction are as accurate as maternal and ultrasound estimates.